The secret mountain - Percival, Tom, 1977- (Naperville, Illinois : Sourcebooks Jabberwocky, 2018)
Jack, Red, and Anansi rescue a lost troll child that was captured as a spy, but what they find out when they return it to Troll Mountain changes everything they have ever known
"Originally published in 2017 in the United Kingdom by Macmillan Children's Books, an imprint of Pan Macmillan"--Title page verso
Ages 7 and up
Keywords: Characters in literature -- Fiction; Magic -- Fiction; Trolls -- Fiction; Lost children -- Fiction; Spies -- Fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Friendship -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Magic -- Juvenile fiction; Trolls -- Juvenile fiction; Missing children -- Juvenile fiction; Spy stories; Fiction